Doctor Jekyll [videorecording (DVD)] - Kelly-Mulhern, Dan; Stevenson, Robert Louis, 1850-1894; Izzard, Eddie; Chambers, Scott, 1994-; Duncan, Lindsay (Hammer Films, 2024)
A modern re-imagining of the infamous Dr. Jekyll from Robert Louis Stevenson's 1886 novella The Strange Case of Dr Jekyll and Mr Hyde. Dr Nina Jekyll makes a fortune in the pharmaceutical industry and becomes a household name, but her success comes at a cost. A scandal forces her out of the spotlight and into seclusion. In need of an assistant, Jekyll hires Rob, an ex-con straight out of rehab who is trying to get back on his feet. It soon becomes clear that there are evil forces at play, and Rob's wits are tested in a game of cat-and-mouse with a manipulative entity.